Internalization of Moral Values in the Book of 'Idhoh An Nasyiin to Santri at Madrasah Aliyah Mu'addalah Islamic College Pondok Tremas Pacitan East Java Academic Year 2024/2025 - Fariduddin Attar Bisri; Shokhibul Mighfar (Literacy: Journal of Education and Social Science, 2025)
The internalization of moral values in classical book learning is only theoretical, whereas moral internalization should be done not only theoretically but also practically. Character formation must be done systematically and continuously. The objectives of this Indonesian study are: 1) to determine the process of internalizing moral values in the book 'Idhoh An Nasyiin for male students in class X at Madrasah Aliyah Mu'addalah Islamic Boarding School Tremas Pacitan, East Java, in the 2024/2025 academic year. 2) To identify the inhibiting and supporting factors in the process of internalizing moral values in the book 'Idhoh An Nasyiin for male students in class X at Madrasah Aliyah Mu'addalah Islamic Boarding School Tremas Pacitan, East Java, in the 2024/2025 academic year. This study employs a qualitative descriptive approach. The research was conducted at Madrasah Aliyah Mu'adallah Islamic Boarding School Tremas Pacitan, East Java, from November to May 2025. The subjects of this study are the Ustadz (teachers) and students of MA Mu'adallah Islamic Boarding School Tremas Pacitan. The informants of this study are from MA Mu'adallah Islamic Boarding School Tremas Pacitan. Data collection methods used are observation, interviews, and documentation. Data validity techniques use source triangulation and method triangulation. Data analysis techniques involve three steps: data reduction, data presentation, and drawing conclusions. The results of this study indicate that the process of internalizing moral values in the book Idhoh An Nasyiin to class X students at Madrasah Aliyah Mu'addalah Islamic College Pondok Tremas Pacitan requires a long time and starts from exemplary role models, advice, and habituation from teachers. Supporting factors for the internalization of moral values include teacher exemplary, student interest, and the relevance of the material to daily life. Meanwhile, the inhibiting factors include the lack of maximum teacher explanation due to busyness and the lack of santri interest in implementing the values that have been taught.